In Vitro Kinematic Analysis of Single Axis Radius Posterior-Substituting Total Knee Arthroplasty - Arauz, Paul; Peng, Yun; Castillo, Tiffany; Klemt, Christian; Kwon, Young-Min (The Journal of Knee Surgery, 2020)
This is an experimental study. As current posterior-substituting (PS) total knee arthroplasties have been reported to incompletely restore intrinsic joint biomechanics of the healthy knee, the recently designed single axis radius PS knee system was introduced to increase posterior femoral translation and promote ligament isometry. As there is a paucity of data available regarding its ability to replicate healthy knee biomechanics, this study aimed to assess joint and articular contact kinematics as well as ligament isometry of the contemporary single axis radius PS knee system. Implant kinematics were measured from 11 cadaveric knees using an in vitro robotic testing system. In addition, medial collateral ligament (MCL) and lateral collateral ligament (LCL) forces were quantified under simulated functional loads during knee flexion for the contemporary PS knee system. Posterior femoral translation between the intact knee and the single axis radius PS knee system differed significantly (p < 0.05) at 60, 90, and 120 degrees of flexion. The LCL force at 60 degrees (9.06 ± 2.81 N) was significantly lower (p < 0.05) than those at 30, 90, and 120 degrees of flexion, while MCL forces did not differ significantly throughout the range of tested flexion angles. The results from this study suggest that although the contemporary single axis radius PS knee system has the potential to mimic the intact knee kinematics under muscle loading during flexion extension due to its design features, single axis radius PS knee system did not fully replicate posterior femoral translation and ligament isometry of the healthy knee during knee flexion.
Keywords: medial and lateral collateral ligaments; posterior-substituting total knee arthroplasty; kinematics; force